(3ehGgH GdCagGe aj TQM TQGFY GdESdGes - (3eMeO egOj Hf GdMSf Hf CMeO GdMSjfj GdbRhjfj GdfLaj,J (B1300 (3g` s
(3ChdgG (B:s
(3hCeG GdbSe GdKGdK agh GdHFQ hGdeQGO HGdHFQ s
(3BNQgG (B:s
(3BNQ GdJaGUjd GdhGbYI ai Gdbdjd hdYdg GSJTgO ai QhGjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B114s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B(92) s
Keywords: (3abg GdePGgH GdCNQis